Practices of Speculation Modeling, Embodiment, Figuration - Cortiel, Jeanne (Edition Kulturwissenschaft, 2021)
This volume offers innovative ways to think about speculation at a time when anticipation of catastrophe in an apocalyptic mode is the order of the day and shapes public discourse on a global scale. It maps an interdisciplinary field of investigation: the chapters interrogate hegemonic ways of shaping the present through investments in the future, while also looking at speculative practices that reveal transformative potential. The twelve contributions explore concrete instances of envisioning the open unknown and affirmative speculative potentials in history, literature, comics, computer games, mold research, ecosystem science and artistic practice.